Den etnometodologiske konversationsanalyse som kulturanalytisk metode - Kjærbeck, Susanne (HERMES - Journal of Language and Communication in Business, 1998)
This article will focus on the ethnomethodological conversation analysis (CA) as a method for analysing cultural phenomena in conversation. It will present some of CA’s basic assumptions about the social character of situated interaction and the use of con-text in conversation as well as discuss some recent research projects which, based on the conversation analytical approach, focus on cultural aspects of face-to-face or telephone conversation. Finally, it presents basic methodological aspects of the main traditions within cultural analysis, the functionalist paradigm and the interpretive anthropology, and relate the CA approach to these traditions. It is suggested that CA may make significant contributions to the ongoing discussion of methodology within the fields of cultural analysis and intercultural communication, be it the technical skills for analysing organization or identity in talk in interaction, the approach to context, to the interactive character of communication, or the reflexive understanding of the relationship between social and cultural norms and situated interaction.